Fuqaha’s Perspective on Ju’ala Contract and Its Application in Bank Wakaf Mikro in Indonesia - Rahmani, Salma; Nuraeni, Neni; Januri, M. Fauzan (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2024)
The understanding of the ju'alah contract in Islam has been a focal point of debate and analysis in fiqh literature. Ju'alah, as a form of promise to provide compensation for tasks or work performed, holds significant implications in Sharia finance practices, including Bank Wakaf Mikro. From the perspective of scholars, there are various views regarding the legal principles and implications of the ju'alah contract, often reflecting differences among schools of thought. This diversity of opinions raises questions regarding the pillars, conditions, and legal implications of ju'alah transactions. The objective of this study is to delve deeper into scholars' comprehension of the ju'alah contract, its distinctions from the ijarah contract, and its application in Bank Wakaf Mikro in Indonesia. In this study, a qualitative approach is utilized, employing a descriptive-analytical method, where data is obtained through library research methods. The research findings indicate that the arguments presented by the Maliki and Syafi'i scholars regarding ju'alah appear to be stronger due to being grounded on more solid reasoning, both in terms of evidence and societal needs. Furthermore, in analyzing the practices of Bank Wakaf Mikro, conformity with the principles of the ju'alah contract is found, both in terms of its pillars and conditions. Among the various scholars' opinions on the ju'alah contract, it is evident that the Syafi'i scholars' views are more aligned with the practices carried out by Bank Wakaf Mikro support programs.